Fascaplysin Induces Caspase Mediated Crosstalk Between Apoptosis and Autophagy Through the Inhibition of PI3K/AKT/mTOR Signaling Cascade in Human Leukemia HL‐60 Cells. Issue 6 (June 2015) - Kumar, Suresh; Guru, Santosh Kumar; Pathania, Anup Singh; Manda, Sudhakar; Kumar, Ajay; Bharate, Sandip B.; Vishwakarma, Ram A.; Malik, Fayaz; Bhushan, Shashi
ABSTRACT In this study, we for the first time explored the cellular and molecular mechanism of anticancer properties of fascaplysin, a marine sponge‐derived alkaloid. Our study demonstrated that fascaplysin induced a cooperative interaction between apoptotic and autophagic pathways to induce cytotoxicity in HL‐60 cells. Fascaplysin treatment not only activated pro‐apoptotic events like PARP‐1 cleavage and caspase activation but also triggered autophagy signaling as shown by the increased expression of LC3‐II, ATG7and beclin. Interestingly, it was found that use of pan‐caspase inhibitor completely reversed the fascaplysin mediated cell death as analyzed by MTT and cell cycle assays. It was observed that cell death as well as the expression of pro‐death proteins was partially reversed, when key autophagy mediators ATG7 was silenced by siRNA in fascaplysin treated cells. Cooperative involvement of autophagy and apoptotic signaling in cytotoxicity was confirmed when combined silencing of pro‐apototic (PARP‐1) and autophagic (ATG‐7) signaling by respective siRNA's lead to substantial rescue of cell death induced by fascaplysin. Although, apoptosis and autophagy are two independent cell death pathways, our findings provide detailed insight by which both the pathways acted cooperatively to elicit fascaplysin induced cell death in HL‐60 cells. Our findings provide molecular insight into the anti‐cancer potential of fascaplysin by showing that both autophagic and apoptotic signaling can work together in the induction of cell death. J. Cell. Biochem. 116: 985–997, 2015. © 2015 Wiley Periodicals, Inc.